Effect of dietary fiber levels on bacterial composition with age in the cecum of meat rabbits. Issue 5 (7th August 2018) - Wu, Zhenyu; Zhou, Hailiang; Li, Fuchang; Zhang, Nanbin; Zhu, Yanli
Abstract: This study investigated the influence of dietary fiber levels on the growth performance, digestion, metabolism, and cecal microbial community of rabbits with different diets at different age. The different levels of dietary natural detergent fiber (NDF) were formulated accordingly: 400(A), 350(B), 300(C), 250(D) g/kg original matter basis, respectively; the different ages were 52, 62, and 72 days. With NDF increasing, the average daily feed intake (ADFI) and feed conversion rate (FCR) were increased, whereas average daily gain (ADG) and mortality were decreased ( p  <   0.05). The stomach relative weight, stomach content relative weight, cecal relative weight, and cecal content weight increased with increasing NDF ( p  <   0.05). The NH3 ‐N concentration of cecum dropped when the dietary NDF increased ( p  <   0.05). The diversity of the total microbiota increased significantly in Diets B, C ( p  =   0.011), and reached the lowest in 52 days for all diet groups. The richness index was decreased significantly in Diet A, D ( p  <   0.05) and in 62 days ( p  <   0.001), respectively. The phylum Firmicutes was higher ( p  <   0.01) in rabbits fed Diets B, C than Diets A, D and Bacteroidetes was highest in Diets C, D, and Proteobacteria was the highest in Diet A ( p  <   0.001). Among the classified genera, there were 14 that had levels of abundance of more than 1% and were commonly shared by all samples. Ruminococcus spp. that produced volatile fatty acid (VFA) abundance was highest from Diets B, C at 52 and 62 days. It is interesting to note that Bifidobacterium from Diet C was the most abundant genus during the entire experimental period ( p  <   0.01). The data from Venn diagrams, principal component analysis (PCA), and heat map plots of the bacterial communities showed that there were more groups of shared microbiota with aging. The above results indicate the cecal microbiota controlled by the 350 g/kg NDF diet can prevent gastrointestinal distress and exhibit good production performance. Abstract : Fiber plays a major role in the regulation of control of gut flora and frequency of enteropathy. Understanding the relation between dietary fiber levels and gut microbiota distribution is very important to preventing gastrointestinal distress by adjusting dietary fiber levels.